Correlation Between Ultrasonic Thyroid Anatomy and Parameters of Physical Development of Children During the Second Period of Childhood. - Temirova Nazokat Rustamovna (Academia One, 2023)
The results of the study showed that in the examined male children, a high correlation was found between the total volume of the thyroid gland and anthropometric indicators: height (r=0.91; P≤0.05), body weight (r=0.92; P≤0 .05), body length (r=0.90; P≤0.05), A similar correlation was found in girls between the volume of the thyroid gland and, respectively: height (r=0.95; P≤0.05), body weight (r=0.96; P≤0.05), body length (r =0.92; P≤0.05).
Keywords: children; thyroid gland; ultrasound